1986
DOI: 10.1007/bf00278818
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the repeated primary non-disjunction of chromosome 21 as a result of premature centromere division (PCD)

Abstract: A clinically normal 28-year-old woman had three conceptuses with trisomy 21 and one normal child. She showed minimal cytogenetic evidence of mosaicism: 4% of her blood cells and 6% of skin fibroblasts had trisomy 21. Also, 7% of her blood cells showed aneuploidy of the X chromosome which was associated with premature centromere division (PCD,X); 6% of fibroblasts showed trisomy 18, 10% of fibroblasts showed PCD,21, and 1% PCD,18. It is unlikely that this woman is a constitutional mosaic for trisomies X, 18, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 18 publications
1
22
0
2
Order By: Relevance
“…Two independent de novo events are possible although the likelihood at this young age is quite low. Another possible explanation is gonadal mosaicism [Beratis et al, 1972;Fitzgerald et al, 1986], which could have potentially been proven by molecular marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent de novo events are possible although the likelihood at this young age is quite low. Another possible explanation is gonadal mosaicism [Beratis et al, 1972;Fitzgerald et al, 1986], which could have potentially been proven by molecular marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PCD were usually clinically normal, but there was sometimes an association with multiple spontaneous abortions or sterility (Rudd et al 1983;Gabarron et al 1986). Fitzgerald et al (1986) reported a clinically normal woman with three conceptuses with trisomy 21 who had PCD in some chromosomes. It was proposed that PCD may result in aneuploid cell lines because prematurely separated centromeres apparently cannot attach to the spindle fibers and this produces non-disjunction.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of chromosomal alteration, phenomenon of premature centromere division (PCD) was observed in sporadic Alzheimer disease (SAD) [6,8,12,19]. PCD represents a loss of control over sequential separation and segregation of chromosome centromeres, characterized by distinctive separation of chromosomes earlier than usual [20,21]. This phenomenon shows that deregulation of the time of centromere separation can be considered as a manifestation of CIN leading to aneuploidy [19,22,23,24].…”
Section: Introductionmentioning
confidence: 99%